2007
DOI: 10.1111/j.1600-0560.2007.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous mononuclear cells and eosinophils are significantly increased after warm water challenge in pruritic areas of polycythemia vera

Abstract: PV represents an invisible dermatosis in which the infiltrating mononuclear cells and eosinophils may have a role in warm water-induced pruritus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Histological studies have shown that in patients with PcV cutaneous water stimulation significantly increases the number of mononuclear cells and eosinophilic granulocytes in the papillary bodies [9, 30]. In addition, vasodilatation and edema as well as degranulating mast cells have been found in the dermis [9, 30]. Despite such findings, some of which are also seen in urticaria, patients with AP generally exhibit symptom‐free skin.…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies have shown that in patients with PcV cutaneous water stimulation significantly increases the number of mononuclear cells and eosinophilic granulocytes in the papillary bodies [9, 30]. In addition, vasodilatation and edema as well as degranulating mast cells have been found in the dermis [9, 30]. Despite such findings, some of which are also seen in urticaria, patients with AP generally exhibit symptom‐free skin.…”
Section: Discussionmentioning
confidence: 99%
“…Although 11 of 43 patients with PV reported that AP was induced by any type of water contact, this experience was not observed in the ET group ( P < 0·05). Most other studies indicated that the water temperature had no influence on the occurrence of AP, but some other studies arrived at contrary findings . We showed that warm water was associated with the occurrence of pruritic crisis for more than half of our patients with PV and MF, but it had no influence on patients with ET ( P < 0·05).…”
Section: Clinical Characteristics Of Aquagenic Pruritus (Ap) In Each mentioning
confidence: 99%
“…The pathogenesis of AP remains a subject of debate, including the role of mast cells . The location of AP can be correlated with a difference in the cutaneous distribution of mast cells compared with those in healthy individuals .…”
Section: Clinical Characteristics Of Aquagenic Pruritus (Ap) In Each mentioning
confidence: 99%
“…Evidence raised from recent studies shows that antihistamines may be effective in systemic diseases because mast cells are part of the pruritus induction mechanisms in pruritogenic systemic diseases such as uremic pruritus or polycythemia vera. In the latter it was shown that the JAK2V617F mutation results in increased activation of mast cells [8,9] and that antihistamines may relieve polycythemia vera-associated pruritus [10]. The advantage of the first step with over one third of patients responding is that the substances may be used on-label and side effects are usually not severe.…”
Section: Discussionmentioning
confidence: 99%